2007
DOI: 10.1200/jco.2006.10.3754
|View full text |Cite
|
Sign up to set email alerts
|

Poor Outcome of Hormone Receptor–Positive Breast Cancer at Very Young Age Is Due to Tamoxifen Resistance: Nationwide Survival Data in Korea—A Report From the Korean Breast Cancer Society

Abstract: Younger patients (age < 35) showed worse prognosis than older patients (age, 35 to 50 years) only in the hormone receptor-unknown or hormone receptor-positive subgroups. Adjuvant tamoxifen therapy might provide less survival benefit when added to chemotherapy in very young breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
175
5
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(209 citation statements)
references
References 25 publications
18
175
5
11
Order By: Relevance
“…An approximately similar high percentage of deaths was reported by van der Hage et al in their study group consisting of patients less than 40 years of age [27]. The Korean Breast Cancer Society reported that young age was associated with a greater probability of death in breast cancer patients [31]. Upon analysing tumour subtypes in the group of patients who died we found that of the 25 patients, the highest number of deaths was observed in the LumB subgroup, followed by the TNBC subgroup, LumA subgroup and HER2+ subgroup.…”
Section: Discussionsupporting
confidence: 76%
“…An approximately similar high percentage of deaths was reported by van der Hage et al in their study group consisting of patients less than 40 years of age [27]. The Korean Breast Cancer Society reported that young age was associated with a greater probability of death in breast cancer patients [31]. Upon analysing tumour subtypes in the group of patients who died we found that of the 25 patients, the highest number of deaths was observed in the LumB subgroup, followed by the TNBC subgroup, LumA subgroup and HER2+ subgroup.…”
Section: Discussionsupporting
confidence: 76%
“…In premenopausal women, this delay affects survival and, as a consequence, increases the potential years of life lost 40 . Some studies have shown that premenopausal women more frequently present with tumors of greater size, have a higher number of positive lymph nodes 41,42 , exhibit more aggressive tumors, and have worse prognoses when compared with postmenopausal women 39,43,44 . According to the suggestions of the World Health Organization (WHO) and the Breast Health Global Initiative (BHGI), developing countries should prioritize efforts to detect patients in earlier clinical stages by increasing awareness in women and access to treatment 45 .…”
Section: Diagnosis and Delay Concernsmentioning
confidence: 99%
“…The incidence of breast cancer is still low in Korea, similar to most other Asian countries, while breast cancer is the most frequent cancer in women, and its incidence is increasing rapidly (2,3). The age distribution is also different than in western countries: the median age at diagnosis in Korean women is 45 years, ~15 years younger than American women; 9.5-12% of Korean breast cancers develop before the age of 35, which is much higher than in Western countries (4,5). In histologic subtype, lobular carcinoma is relatively rare in Korea.…”
Section: Introductionmentioning
confidence: 95%